Brauer-Buschke-Fisher Keratoderma - Ahmad Qazi Masood; Hassan Iffat; Majid Imran (Wolters Kluwer Medknow Publications, 2001)
A 40 year old male farmer with brauer-buschke-fisher keratoderma is being reported in view of the rarity of this condition.